Evolution of bacterial meningitis diagnosis in Sao Paulo State-Brazil and future challenges - Maristela Marques Salgado; Maria Gisele Goncalves; Lucila Okuyama Fukasawa; Fabio Takenori Higa; Juliana Thalita Paulino; Claudio Tavares Sacchi (Arquivos de Neuro-Psiquiatria)
Bacterial meningitis (BM) is a severe disease and still represents a serious public health problem with high rates of morbidity and mortality. The most common cases of BM around the world, mainly in Brazil, have been caused by Neisseria meningitidis, Streptococcus pneumoniae, and Haemophilus influenzae type b. Bacterial culture is the gold-standard technique for BM confirmation, but approximately 50% of suspected cases are not culture-confirmed, due to problems related to improper transportation and seeding or previous antibiotic treatment. Immunological methods present low sensitivity and have possibility of cross-reactions. Real time PCR (qPCR) is a molecular technique and has been successful used for BM diagnosis at Instituto Adolfo Lutz in São Paulo State, Brazil, since 2007. The incorporation of qPCR in the Public Health surveillance routine in our state resulted in diminishing 50% of undetermined BM cases. Our efforts are focused on qPCR implementation in the BM diagnostic routine throughout Brazil.